ANALISIS LINGKUNGAN UNTUK MENENTUKAN STRATEGI BISNIS - Sefel, Raja Abiyyu; Aisjah, Siti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
People’s need for smartphones is increasing globally, including in Indonesia. In Riau province, particularly in Pelalawan Regency, there is a business unit that engages in the sales of smartphone peripherals and internet data plan; it is Caghonti Ponsel. The business’ sales during the last six months have not been stable, and this affects its continuity. Using the problem as the research background, this study aims to identify and analyze the strengths, weaknesses, opportunities, and the threats of the business and to recommend the suitable strategy for the company. This qualitative descriptive research uses primary data obtained from interviews, observations, and documentations and secondary data in forms of books, journals, articles, etc. the instruments of the analysis are IFE Matrix, EFE Matrix, SWOT Matrix, and QSPM Matrix. The results of the analysis indicate that the most suitable strategy for Caghonti Ponsel is market penetration.